Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1128/jcm.39.5.1788-1790.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage and Type of Blood Collection Tubes on Hepatitis C Virus Level in Whole Blood Samples

Abstract: In this study, we compared serum hepatitis C virus (HCV) RNA concentrations with HCV RNA concentrations in whole blood collection tubes, including two different types of EDTA tubes and nucleic acid stabilization tubes (NASTs). We also investigated the impact of a processing delay on HCV RNA concentration in these tubes. In NASTs, the mean HCV RNA concentration was comparable to the mean serum HCV RNA concentration at "date zero." In EDTA tubes, mean baseline HCV RNA concentrations were higher. Storage at room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Conditions for handling, storage, and extraction have been found to be crucial to the performance of PCR assays of patient material (6,9,20). Our study demonstrated that B. burgdorferi DNA can be detected in urine by PCR assay when certain conditions are fulfilled, such as avoidance of the first morning urine, centrifugation at 36,000 ϫ g, extraction by DNAzol, and avoidance of freezing for Ͼ3 months.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions for handling, storage, and extraction have been found to be crucial to the performance of PCR assays of patient material (6,9,20). Our study demonstrated that B. burgdorferi DNA can be detected in urine by PCR assay when certain conditions are fulfilled, such as avoidance of the first morning urine, centrifugation at 36,000 ϫ g, extraction by DNAzol, and avoidance of freezing for Ͼ3 months.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation of this study is that we did not analyze RNA stability in EDTA blood samples. However, a previous study found HCV RNA stable in EDTA blood for up to 96 h (9), similar to what we observed for DNA targets.…”
mentioning
confidence: 36%
“…Although there are published guidelines for the collection, transport, and storage of specimens for molecular tests, described by CLSI (4), they are based mostly on opinions and limited experimental data. Published data on the stability of pathogen-specific amplification targets are also limited to individual pathogens and/or specimen types (3,4,(6)(7)(8)(9)(10)12). Therefore, in this study, we undertook a broader study to compare the stability of extracted and unextracted clinical samples over time and at different temperatures.…”
mentioning
confidence: 99%
“…The clinical utility of RNA amplification based assays by RT-PCR depends on the specificity, sensitivity, reproducibility, and stability of viral RNA in blood [4]. The stability of viral RNA in blood is dependent on sample storage and shipping conditions and the type of blood collection device [5]. Poor specimen handling, sample processing, storage conditions or use of an incompatible blood collection tube may result in viral RNA degradation which may lead to false-negatives or an underestimation of viral RNA concentration.…”
Section: Introductionmentioning
confidence: 99%